2020
DOI: 10.25259/sni_606_2020
|View full text |Cite
|
Sign up to set email alerts
|

Acute handlebar syndrome: Two extremes of a challenging diagnosis

Abstract: Background: Ulnar nerve mononeuropathy diagnosis can be challenging depending on where neural lesion is present. Repetitive trauma during cycling is a rare cause of ulnar neuropathy. Case Description: We describe two patients who developed the handlebar syndrome, an ulnar nerve palsy at Guyon’s canal after cycling. The first patient had the syndrome after a short-distance ride and she was treated surgically, while the second patient developed the classical syndrome after a long ride and received conservati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…The differential diagnosis for cyclist palsy is broad. Compressive structural pathology at Guyon canal should be considered, such as ganglion cysts, hamate fractures, vascular malformations, and lipomas 7,18 . Median nerve entrapment should also be considered as it has been demonstrated that cyclists can developed electrodiagnostic evidence of carpal tunnel syndrome after long-distance rides 19–21 .…”
Section: Differential Diagnosismentioning
confidence: 99%
See 4 more Smart Citations
“…The differential diagnosis for cyclist palsy is broad. Compressive structural pathology at Guyon canal should be considered, such as ganglion cysts, hamate fractures, vascular malformations, and lipomas 7,18 . Median nerve entrapment should also be considered as it has been demonstrated that cyclists can developed electrodiagnostic evidence of carpal tunnel syndrome after long-distance rides 19–21 .…”
Section: Differential Diagnosismentioning
confidence: 99%
“…In the setting of intrinsic hand weakness, magnetic resonance imaging of the cervical spine should be considered to rule out conditions such as cervical myelopathy and radiculopathy. However, once both neurologically catastrophic pathology and more common pathology have been ruled out adequately, then nerve conduction studies and electromyography may be pursued to best localize the presumed peripheral nerve lesion 7 …”
Section: Investigationsmentioning
confidence: 99%
See 3 more Smart Citations